A Microplate-Based Expression Monitoring System for Arabidopsis NITRATE TRANSPORTER2.1 Using the Luciferase Reporter - Yoshiaki Ueda; Shuichi Yanagisawa (Bio-Protocol)
Gene expression analysis is a fundamental technique to elucidate the regulatory mechanisms of genes of interest or to reveal the patterns of plant response to environmental stimuli. Traditionally, gene expression analyses have required RNA extraction, followed by cDNA synthesis and qPCR analyses. However, this conventional method is costly and time-consuming, limiting the amount of data collected. The protocol outlined in this study, which utilizes a chemiluminescence system, offers a cost-effective and rapid method for assessing the expression of Arabidopsis (Arabidopsis thaliana) genes, exemplified by analyzing the nitrate-inducible expression of a major nitrate transporter gene, nitrate transporter 2.1 (NRT2.1). A reporter construct, containing the NRT2.1 promoter fused to the firefly luciferase gene, was introduced into wild-type and mutant Arabidopsis plants. Seeds obtained from the transgenic lines were grown for 3 days in 96-well microplates containing a nitrate-free nutrient solution. After 3 days, the nutrient solution was replaced with a fresh batch, which was supplemented with luciferin potassium. One hour later, nitrate was added at various concentrations, and the temporal expression pattern of NRT2.1 was analyzed by monitoring the chemiluminescence signals. This method allowed for the cost-effective, quantitative, and high-throughput analysis of NRT2.1 expression over time under the effects of various nutrient conditions and genetic backgrounds.